2016
DOI: 10.1111/jfpp.12895
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modelling of Osmotic Dehydration Kinetics of Apple Cubes

Abstract: Apple cubes were osmotically dehydrated at 25, 40 and 60C, using sucrose or sorbitol, and the mass ratio of sample to solution of 1:4 and 1:10, at atmospheric pressure or vacuum pressure of 150 mbar. Six mathematical models were tested to describe the mass transfer kinetics of water loss (WL) and sugar gain (SG). Crank's, Azuara's, Peleg's, Page's and Weibull's models could fit well the experimental data, but the Penetration model resulted in a poor fit. The mass ratio of sample to solution did not have an inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
58
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 47 publications
21
58
2
1
Order By: Relevance
“…The experiments were carried out at atmospheric pressure and at 60 ºC, using constant agitation of 50 r.p.m. The experimental conditions had been optimized in a previous work (ASSIS et al, 2017a).…”
Section: Osmotic Pre-treatmentmentioning
confidence: 99%
“…The experiments were carried out at atmospheric pressure and at 60 ºC, using constant agitation of 50 r.p.m. The experimental conditions had been optimized in a previous work (ASSIS et al, 2017a).…”
Section: Osmotic Pre-treatmentmentioning
confidence: 99%
“…During the osmotic dehydration of most fruits, a rapid water loss can be noted during the first two hours of the process (ASSIS et al, 2017;SILVA et al, 2012). However, physalis did not present this behaviour.…”
Section: Resultsmentioning
confidence: 87%
“…Doymaz et al [5] and Murthy and Manohar [7] found that the effective diffusivity correlated well with the microwave power and presented values for Ea of around 20 kW.kg -1 during the MWD of green bean and mango ginger, respectively. These findings may be explained by the fact that Crank's is a phenomenological model (Assis et al [10]) and would allow to obtain a correlation with physical meaning, while modified Page's is just an empirical one (as stated above, Crank's model could not produce a good fit of the experimental data).…”
Section: Mass Transfer Kineticsmentioning
confidence: 82%
“…From previous experiments [10], the osmotically treated samples presented a water loss of 63% for both solutions used and a solid gain of 11% and 16% for sucrose and sorbitol, respectively, after 8 h of the OD process.…”
Section: Mass Transfer Kineticsmentioning
confidence: 99%